THE ROLE OF INTERNATIONAL LAW IN COMBATING CLIMATE CHANGE - Emin Aliyev Sabit (Modern American Journals, 2025)
This article examines the role of international law in combating global climate change. It explores the legal aspects of global climate change, international agreements and their impact on national legislations, as well as the challenges and future prospects of international law. The study highlights the solutions to global problems that can be achieved through joint actions of countries in the fight against climate change.
Keywords: Global climate change, global problems, international law.